Application of Information Systems, Internal Control, Risk Assessment, and Internal Audit for Collection Effectiveness of Accounts Receivable - Hasanah, Uswatun; Sari, Imelda; Zhafiraah, Nazma Riska (Research of Accounting and Governance, 2024)
The aim the purpose of this study was to ascertain how internal control and accounting information systems, risk assessment and internal auditing influence the effectiveness of receivables collection. This study was conducted at PT. Puninar Infinite Raya uses the use of internal audit, risk assessment, internal control, and accounting information systems as independent variables and the effectiveness of the collection of accounts receivable as dependent variables. The sample in the study amounted to 42 people. The questionnaires received back from the respondents were 42 people. There is one analysis model of the data processing method used, namely the model for multiple regression analysis. According to the study's findings, the use of accounting information systems significantly and negatively affects the efficiency of collecting receipts; on the other hand, internal control significantly and favorably affects the efficiency of collecting receivables, and risk assessment affects the efficiency of collecting receivables. The efficiency of receivables collection is impacted concurrently by the use of accounting information systems, internal control, risks associated with their implementation, risk assessment, and internal audit. The study's managerial implications include the use of information systems. Such as operating efficiency and real-time monitoring. Internal control such as fraud prevention, legal compliance.